DETERMINAN PERILAKU OPPORTUNISTIC PENYUSUN ANGGARAN CALON INCUMBENT TERKAIT PILKADA SERENTAK TAHUN 2015 - Suartini, Ni Kadek Ayu; Ariyanto, Dodik; Sari, Maria M. Ratna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This research aims to examine and determine the effect of PAD, DAK and SiLPA on opportunistic behavior of incumbent budget compiler related local elections simultaneously in 2015 at Regency/City in Indonesia. The amount of the populations were Regency/City in Indonesia that followed the elections simultaneously in 2015. The sampling method used is purposive sampling. Based on these criteria, the number of samples in the study of 45 regions comprising 34 Regencys and 11 Cities. This research used the secondary data. The data used are the realization of the budget that includes the PAD, DAK, SiLPA, education, health, infrastructure, grants and social assistance in 2013-2015. The analysis technique used is the multiple regression analysis. The result obtained are changes PAD, DAK and SiLPA positive influence on opportunistic behavior of incumbent budget compiler at Regency/City in Indonesia.
Keywords: Local elections simultaneously, APBD